Philippe et Françoise sont-ils mieux appréciés à l’école qu'Illyas et Yasmina ? - Iuliana Lunca Popa (Recherches en Éducation)
The problem of inequality in school brings us inevitably to the ethnic issue, a taboo and a phenomenon described as “invisible” in France. Hence, rather than dealing directly with this very delicate problem an approach based on the use of indirect indicators for the ethnic origin (such as the consonance of the name / first name), is required/preffered. Assuring the anonymity of students and thus operating as a screen to students’ identities, technologies constitute an element able to break the traditional teacher-student relationship. In this new work and learning environment provided by the use of technology some questions rise: Teachers representations on the cognitive potential of students are changing? They are any changes in representations with respect to cognitive performance of students due to the supposed ethnic origin of the student?